(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. Marketing in the economic system forms and directs all other functions to satisfy the needs of the consumer and turns them into income of the enterprise. The basis for achieving this goal is to establish and maintain effective relations with consumers for mutual long-term benefit. It is customers who form the key values of the enterprise and are the source of its economic growth. The purpose of the article is to determine the features of the implementation by enterprises of a customer-oriented approach in a modern business environment. Results. The prerequisites and peculiarities of implementation of the concept of marketing relations and direction of improvement of marketing management in the context of this concept have been investigated. The emergence and development of marketing relations are due to significant changes in business: the development of information technologies, the increase in the complexity of relations, changes in the management of the quality of products (services), the expansion of the service sector and the like. The marketing interests of many firms shift towards the process of debugging the relationships between all market entities and maximizing the beneficial effect of their interaction. Approaches to understanding the concept of client-oriented and its evolutionary development are summarized. Factors affecting the transformation of relationship marketing functions have been identified. These include macro-environment factors and microenvironment factors. It is proposed to consider the system of marketing relations as a set of complex connections within the enterprise and with market entities at the micro and macro level. Conclusions. The main goal of customer-oriented marketing management remains the creation of an effective marketing interaction system. The increased attention of scientists and the business environment in the client-oriented approach is due to the growth of the general level and intensity of competition, the complication of market behavior of consumers, the rapid development of information and communication technologies, and the reduction of the product life cycle.